Management of Destructive Colon Injuries after Damage Control Surgery - Chamieh, Jad; Prakash, Priya; Symons, William J. (Clinics in Colon and Rectal Surgery, 2018)
After the World War II, fecal diversion became the standard of care for colon injuries, although medical, logistic, and technical advancements have challenged this approach. Damage control surgery serves to temporize immediately life-threatening conditions, and definitive management of destructive colon injuries is delayed until after appropriate resuscitation. The bowel can be left in discontinuity for up to 3 days before edema ensues, but the optimal repair window remains within 12 to 48 hours. Delayed anastomosis performed at the take-back operation or stoma formation has been reported with variable results. Studies have revealed good outcomes in those undergoing anastomosis after damage control surgery; however, they point to a subgroup of trauma patients considered to be “high risk” that may benefit from fecal diversion. Risk factors influencing morbidity and mortality rates include hypotension, massive transfusion, the degree of intra-abdominal contamination, associated organ injuries, shock, left-sided colon injury, and multiple comorbid conditions. Patients who are not suitable for anastomosis by 36 hours after damage control may be best managed with a diverting stoma. Failures are more likely related to ongoing instability, and the management strategy of colorectal injury should be based mainly on the patient's overall condition.
Keywords: damage control laparotomy; abdominal trauma; colon trauma; ostomy; anastomosis